Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0078235
|View full text |Cite
|
Sign up to set email alerts
|

Protein N-Myristoylation Plays a Critical Role in the Endoplasmic Reticulum Morphological Change Induced by Overexpression of Protein Lunapark, an Integral Membrane Protein of the Endoplasmic Reticulum

Abstract: N-myristoylation of eukaryotic cellular proteins has been recognized as a modification that occurs mainly on cytoplasmic proteins. In this study, we examined the membrane localization, membrane integration, and intracellular localization of four recently identified human N-myristoylated proteins with predicted transmembrane domains. As a result, it was found that protein Lunapark, the human ortholog of yeast protein Lnp1p that has recently been found to be involved in network formation of the endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 50 publications
(57 reference statements)
2
57
0
Order By: Relevance
“…The mammalian Lnp (mLnp1) protein features an N‐terminal myristoylation site, and ER network changes induced by overexpression of LNP proteins were significantly inhibited by the mutation of protein N ‐myristoylation which rendered this motif nonfunctional (Moriya et al ., 2013). Yeast Lnp1p protein, by contrast, does not feature this motif (Moriya et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mammalian Lnp (mLnp1) protein features an N‐terminal myristoylation site, and ER network changes induced by overexpression of LNP proteins were significantly inhibited by the mutation of protein N ‐myristoylation which rendered this motif nonfunctional (Moriya et al ., 2013). Yeast Lnp1p protein, by contrast, does not feature this motif (Moriya et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Yeast Lnp1p protein, by contrast, does not feature this motif (Moriya et al ., 2013). Arabidopsis LNP proteins similarly do not possess an N‐terminal glycine and therefore are predicted to lack a myristoylation site as shown for mLnp1 (Moriya et al ., 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, co-translational modification of protein is required to carry out some specific functions such as protein trafficking, aggregation, and affinity for membrane attachment (Adamson et al 1992;Löfke et al 2013). These co-translational modifications may be either palmitoylation or myristoylation (Linder & Deschenes 2007;Wright et al 2010;Moriya et al 2013). Sequence analysis revealed the presence of N-terminal palmitoylation sites in HcCCR1 (SSNGMTVCVTGAGGF) and HcCCR2 (CSNGTTVCVTGAGGF) protein.…”
Section: Discussionmentioning
confidence: 99%
“…The LANCL2 protein is associated with the plasma membrane through N-terminal myristoylation and a basic phosphatidylinositol phosphate-binding site (21). However, protein lipidation, a typical feature of peripheral membrane proteins, has been recently observed in integral membrane proteins as well (22), and previous immunofluorescence studies performed on LANCL2-overexpressing cells were inconclusive regarding the transmembrane or peripheral position of LANCL2 (18). Here, we investigated LANCL2 localization in human erythrocytes, and found that LANCL2 is a peripheral protein attached to the intracellular side of the RBC membrane; thus, for ABA to enter into RBC and bind to its receptor, ABA transport across the plasma membrane is necessary.…”
mentioning
confidence: 99%